KINERJA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH DALAM MENERAPKAN SISTEM MERIT BERBASIS TALENT SCOUTING DI KABUPATEN TEGAL - Dedi Kusmana; Fredy Prasetyawan (Jurnal Media Birokrasi, 2021)
The purpose of writing the final report aims to analyze the performance of BKD in implementing a talent scouting-based Merit System in Tegal Regency, as well as to answer problems that have been formulated and provide efforts related to these problems and obstacles. The theory used by the writer is the theory of performance according to Agus Dwiyanto 2008. The method used is a descriptive research method with an inductive approach. The data collection techniques used were interviews, observation, and documentation. While the data analysis techniques used are data reduction, data display, and conclusion / verification.The results showed that of the five performance indicators, only the responsiveness indicator was lacking. The conclusion is that the performance of the BKD of Tegal Regency in implementing a merit system based on talent scouting in Tegal Regency has been running well but there are still obstacles in terms of infrastructure and individual apparatus such as lack of motivation in following the selection process. Efforts have been made, namely leasing infrastructure and socializing talent scouting. Keywords: Apparatus, Merit system based on talent scouting, Performance